SMG602 - Recreation Resource Management / Faculty of Sports Science & Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2021)
This course will investigate the multiple elements of recreation resources management. It is also designed to give students an understanding of the skill necessary for planning, designing, maintaining and managing recreational resource areas. Topics covers include the foundation of outdoor recreation resources, recreation resources management and approaches, and trail planning and development. Additional areas examined will include trends and issues involve in recreation resources.